What, when, and how food and beverage are advertised on Ghanian television. - Morgan Boncyk; Krystal K Rampalli; Marian N Winters; Muskaan K Makkar; Silver Nanema; Gideon S Amevinya; Amos Laar; Edward A Frongillo; Christine E Blake (PLoS ONE)
Food marketing has increased volume, precision, and reach to influence viewers' food attitudes, beliefs, and eating behaviors. What and how much people eat has implications for health. While many countries regulate food advertising to protect consumers and encourage healthy eating, Ghana has none. Understanding the content and framing of food and beverage advertisements can inform the development of effective policies and practices that encourage healthier diets. This content analysis examines the foods and beverages advertised, their timing, and marketing techniques on Ghanaian television. From February to May 2020, 486 hours of advertisements were recorded. Advertisements with ≥1 actors were coded for food type, actor characteristics (i.e., body size, gender, age, race), and marketing techniques (i.e., promotional characters, premium offers, goal frames). A total of 607 advertisements with 2,043 actors were analyzed. Two-thirds (66.8%) promoted foods categorized as unhealthy. Sugar-sweetened beverages (22.6%) were most frequent, followed by grains high in sugar and low in fiber (13.2%), recipe additions (13.1%), and supplements (10.2%). Half (52.9%) of advertisements used persuasive marketing strategies. Most actors were classified as underweight (72.1% v. 20.5% normal weight, 7.4% overweight/obese) with a balanced gender distribution (49.1% female). Most advertisements aired during evenings (37.7%) and weekdays (69.5%). Morning advertisements promoted more healthy foods, whereas evening and night advertisements promoted more unhealthy foods. Gain goal frames were most common for healthy foods (p < 0.001), hedonic frames for unhealthy foods (p < 0.001), and normative frames showed no difference (p = 0.54). Underweight actors frequently appeared in unhealthy advertisements (68.3% v. 56.0% normal weight, 59.0% overweight/obese), whereas normal-weight (44.0%) and overweight/obese actors (41.0% v. 31.7% underweight) appeared in healthy advertisements. Persuasive marketing strategies were frequently advertised with unhealthy foods (59.9%) and overweight/obese (54.9%) and male actors (53.6%). This study highlights the need for effective policies to regulate food marketing, promoting healthier diets and realistic body expectations.